Matériel et conditions de reproduction du ver à soie de chêne Antheraea pernyi Guer (Bombycidae) - Nueleanu, Veturia – Ileana (Acta Agraria Debreceniensis, 2003)
In this study we highlighted the conditions that need to be fulfilled in order to have successful oak silkworm reproduction. Thus, conditions for best cocoon hibernation should be as follows: strata of 10-15 cm with optimal temperature around 0oC, relative humidity of 60-70%. The cocoons must be moved every 10 days and must also be daily aired. Butterfly mating should take place either the night of their coming out or the second day. It takes 14-15 hours; male butterflies outnumber females by 10%. After mating, the optimal temperature for laying eggs is 18-20oC; relative humidity is 80%; egg laying takes place in the dark.